Pengaruh financial knowledge, financial attitude, dan income terhadap financial management behavior pengguna Shopee PayLater - Gumitasari, Virdia; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2024)
PayLater has become one of the most popular and widely used payment methods in e-commerce. The increasing trend of using PayLater platforms is because of their flexibility as an alternative payment service. Amidst the advantages offered, PayLater can also lead to behaviors such as late or failed payments. Issues with the use of PayLater arise because of poor financial management behavior among its users. Therefore, this study aims to examine the influence of financial knowledge, financial attitude, and income on the financial management behavior of Shopee PayLater users. The population of this study consists of 68 undergraduate students from a university in Surabaya, which were calculated using Isaac and Newton with probability sampling techniques. The data were analyzed using descriptive analysis and multiple linear regression analysis with IBM SPSS version 25. The results of this study show that financial attitude has a significant positive influence on financial management behavior. Undergraduate students in Surabaya who use Shopee PayLater with a positive financial attitude tend to exhibit good financial behavior. However, financial management behavior is not influenced by financialknowledge or income. The level of financial knowledge and income does not affect the financial managementbehavior of undergraduate students in Surabaya who use Shopee PayLater.